Rural-urban health differences among aging adults in India - Supa Pengpid; Karl Peltzer (Heliyon, 2024)
Background: The aim of this study was to determine the rural-urban health differences among aging adults in India. Methods: The national cross-sectional data of 67,489 individuals (≥45 years) in 2017–2018 from 35 states and union territories of India (excluding Sikkim) in 2017–2018 were analysed. Various sociodemographic data, well-being indicators, lifestyle factors and physical conditions were assessed by face-to-face interviews and physical measurement. Univariable and multivariable logistic regression was utilized to assess the predictors between residence status (rural dweller, urban migrant, and urban dweller) and various health indicator outcomes. Results: Majority (70.4 %) of the participants lived in rural areas, 10.3 % were urban migrants and 19.3 % urban dwellers. In the multivariable logistic regression analysis, urban migrants and urban dwellers had a higher self-rated health status, cognitive functioning, physical inactivity, overweight or obesity and abdominal obesity than rural dwellers, while urban migrants and/or urban dwellers had lower functional disability, insomnia symptoms, current smokeless tobacco use, current smoking, heavy episodic drinking and underweight than rural dwellers. Furthermore, urban migrants and/or urban dwellers had higher odds of diabetes, hypertension, heart disease, cancer, high cholesterol than rural dwellers, while urban migrants and/or urban dwellers had lower odds of persistent headaches, major injury, recurrent fall, physical pain, periodontal disease, vision impairment, and gastrointestinal problems than rural dwellers. Conclusion: Among 30 health indicators assessed, 16 had an urban migrant and/or urban dweller advantage, 8 had urban migrant and/or urban dweller penalty, and 6 did not differ between rural-urban groups. Public health promotion and health care should address differing health care needs of rural and urban middle-aged and older adults.